Antibacterial composite material based on hydrogen bond organic framework as well as preparation and application of antibacterial composite material

By using composite materials based on hydrogen bond organic frameworks in antibacterial materials, encapsulate glucose oxidase and adsorb the copper sulfide wrapped in chitosan on the surface, the problem of poor effect of existing antibacterial materials in the bacterial microenvironment is solved, and the multivariate synergistic antibacterial effect is achieved and good biocompatibility is shown.

CN119746065AActive Publication Date: 2025-04-04HEBEI MEDICAL UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510041344.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing antibacterial materials are not effective in bacterial microenvironment, and photothermal therapy may damage normal cells and affect the therapeutic effect.

Method used

An antibacterial composite material based on a hydrogen bond organic framework is adopted. The material is encapsulated with glucose oxidase and adsorbed with chitosan-encapsulated copper sulfide on the surface. It provides hydrogen peroxide through the bacterial microenvironment, increases acidity, and achieves multivariate and synergistic antibacterial through the bacterial microenvironment.

Benefits of technology

Under 808nm near infrared light irradiation, the composite material has obvious antibacterial effects on both Gram-positive and negative bacteria, and shows good biocompatibility and hemocompatibility, providing an effective treatment plan for alternative antibiotics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to an antibacterial composite material based on a hydrogen bond organic framework and preparation and application thereof, and belongs to the technical field of material chemistry and biology. According to the antibacterial composite material based on the hydrogen bond organic framework, the hydrogen bond organic framework serves as a main body, glucose oxidase is packaged on the main body, chitosan-wrapped ultra-small copper sulfide is adsorbed on the surface, and the preparation method of the antibacterial composite material based on the hydrogen bond organic framework is disclosed. According to the antibacterial composite material disclosed by the invention, the antibacterial synergistic effect is achieved through combination of a chemical kinetic therapy, a photothermal therapy and a hunger therapy, and the antibacterial composite material has a good antibacterial effect. Experiments prove that the antibacterial composite material disclosed by the invention has an obvious antibacterial effect on gram-positive bacteria staphylococcus aureus and gram-negative bacteria escherichia coli, and has good biocompatibility and blood compatibility through preliminary evaluation, and a foundation is laid for preparation of corresponding antibacterial drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material chemistry and biology, and in particular to an antibacterial composite material based on a hydrogen bond organic framework and the preparation and application thereof. Background Art

[0002] Bacterial infection has been a serious health problem for thousands of years. It can cause various diseases such as non-healing wounds, pneumonia, and soft tissue infections. Antibiotics are widely used in clinical practice as a traditional treatment method, but improper or excessive use of antibiotics leads to the emergence of multi-drug resistant strains, which seriously threaten human life and health. The World Health Organization predicts that the number of deaths caused by drug-resistant bacteria will reach 10 million in 2050, and drug-resistant bacterial infections will become the most serious health crisis. Therefore, there is an urgent need to explore alternative treatments to fight bacterial infections.

[0003] Faced with the complex bacterial microenvironment, chemokinetic antibacterial has been widely studied in recent years. Chemokinetic antibacterial uses the slightly acidic environment of bacteria to exert the Fenton or Fenton-like effect of metals to produce highly toxic hydroxyl radicals and kill bacteria. However, a single treatment mode is often ineffective. By combining with other therapies such as photothermal therapy, photodynamic therapy, and starvation therapy to exert synergistic effects, an antibacterial effect of 1+1>2 can be achieved. CN 114984241 A discloses a chitosan / manganese dioxide / glucose oxidase nanocomposite material, which is composed of chitosan nano-microspheres, and manganese dioxide and glucose oxidase loaded on the surface of chitosan nano-microspheres. It can achieve the dual antibacterial and anti-tumor effects of starvation therapy and chemokinetics. Since the Fenton-like effect of manganese dioxide is weak and glucose oxidase is exposed to the outside, the enzyme activity is easily affected, which in turn affects the catalytic activity of the material.

[0004] Although chemokinetics and photothermal therapy are of great significance in replacing antibiotic treatment, they are subject to many limitations. Insufficient endogenous hydrogen peroxide in the bacterial microenvironment and low acidity greatly reduce the antibacterial effect of chemokinetics. Although photothermal therapy has excellent antibacterial effects, excessively high temperatures often damage normal cells and affect the treatment effect.

[0005] Based on the above background, the present application discloses an antibacterial composite material based on a hydrogen-bonded organic framework, which can utilize the bacterial microenvironment to provide hydrogen peroxide, increase acidity, and achieve multi-component synergistic antibacterial effects in synergistic ways with mild light and heat. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide an antibacterial composite material based on a hydrogen bond organic framework and its preparation and application.

[0007] To solve the above problems, the technical solution adopted by the present invention is: Technical Theme 1 An antibacterial composite material based on a hydrogen-bonded organic framework, wherein the composite material is based on the hydrogen-bonded organic framework, glucose oxidase is encapsulated in the framework, and copper sulfide wrapped in chitosan is adsorbed on the surface; The building block of the hydrogen bond organic framework is 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene.

[0008] As a further improvement of the present invention, the loading amount of glucose oxidase in the composite material is 2.35%wt-9.97%wt.

[0009] Technical Theme 2 A method for preparing an antibacterial composite material based on a hydrogen-bonded organic framework as described in the first technical subject, comprising the following steps: S1: 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene is dissolved in solvent I as solution A, and glucose oxidase is dispersed in water as solution B; S2: quickly add solution B prepared in S1 into solution A, stir for 5-10 minutes, place in the dark for 20-30 minutes, centrifuge and wash with water to obtain GOx@HOF; S3: Add copper chloride and sodium citrate to water in sequence, stir evenly, then add sodium sulfide, stir for 10-12 hours, centrifuge, wash with water, and dry to obtain copper sulfide; S4: The copper sulfide obtained in S3 is dispersed in the chitosan solution and stirred at 1000-1200 rpm for 2-4 hours, centrifuged, washed with water, and dried to obtain CuS@CS; S5: Add GOx@HOF obtained in S2 and CuS@CS obtained in S4 into water, disperse them evenly by ultrasonication, stir at 1200-1500 rpm for 10-14 h, centrifuge and wash with water to obtain GOx@HOF-CuS@CS.

[0010] As a further improvement of the present invention, the mass ratio of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene to glucose oxidase in S2 is 1:0.1-0.7; The molar ratio of copper chloride: sodium citrate: sodium sulfide in S3 is 0.9-1.1:0.6-0.9:1; The mass ratio of copper sulfide to chitosan in S4 is 1:3-8; The mass ratio of GOx@HOF to CuS@CS in the S5 is 1:1.5-2.5.

[0011] As a further improvement of the present invention, solvent I is selected from DMF, DMAc, NMP, DMSO; the volume ratio of solution A to solution B in S2 is 1:8-10; the mass volume ratio of GOx@HOF to water in S5 is 4 mg:5-20 mL.

[0012] As a further improvement of the present invention, the mass volume ratio of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene to solvent I in solution A is 5 mg:400-800 μL; As a further improvement of the present invention, the centrifugal speed in S2 is 12000-13000 rpm, and the centrifugal time is 10-15 min; In S3, the centrifugal speed is 13000-15000rpm and the centrifugal time is 20-30min; In S4, the centrifugal speed is 13000-15000rpm and the centrifugal time is 20-30min; In S5, the centrifugal speed is 11000-13000rpm and the centrifugal time is 10-15min.

[0013] As a further improvement of the present invention, the concentration of sodium citrate in S3 is 0.1-0.4 mg / mL.

[0014] As a further improvement of the present invention, the chitosan solution in S4 is prepared by dissolving chitosan in a 0.5-1.5% glacial acetic acid solution, and the concentration of chitosan is 5-50 mg / mL.

[0015] As a further improvement of the present invention, the concentration of chitosan is 5-8 mg / mL.

[0016] As a further improvement of the present invention, the mass ratio of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene to glucose oxidase in S2 is 1:0.5; The molar ratio of copper chloride: sodium citrate: sodium sulfide in S3 is 1.05:0.78:1 The mass ratio of copper sulfide to chitosan in S4 is 1:5; The mass ratio of GOx@HOF to CuS@CS in S5 is 1:2.

[0017] Technical Theme 3 An application of an antibacterial composite material based on a hydrogen-bonded organic framework as described in Technical Topic 1 in the preparation of antibacterial drugs.

[0018] The beneficial effects of adopting the above technical solution are: The invention discloses an antibacterial composite material based on a hydrogen bond organic framework, which has glucose oxidase activity, can consume glucose, exert starvation antibacterial effects, produce gluconic acid, regulate bacterial microenvironment, and provide substrates for chemical kinetics.

[0019] The loaded ultrasmall copper sulfide has excellent chemical kinetics and photothermal properties. The ultrasmall copper sulfide is modified by chitosan with antibacterial activity and loaded onto the surface of the hydrogen-bonded organic framework, thereby achieving multi-component synergistic antibacterial properties of the antibacterial composite material based on the hydrogen-bonded organic framework and having a broad-spectrum antibacterial activity.

[0020] The GOx@HOF-CuS@CS prepared in this example encapsulates glucose oxidase and has stable catalytic performance. Under 808nm near-infrared light irradiation, the antibacterial composite material has obvious antibacterial effects on Gram-positive bacteria Staphylococcus aureus and Gram-negative bacteria Escherichia coli, and preliminary evaluation shows that it has good biocompatibility and blood compatibility, laying a foundation for the preparation of corresponding antibacterial drugs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 TEM images of materials prepared in a specific embodiment of the present invention, wherein A is CuS@CS prepared in Example 1, B is GOx@HOF prepared in Example 1, C is GOx@HOF-CuS@CS prepared in Example 1, and D is HOF prepared in Comparative Example 1; Figure 2 It is a structural comparison diagram of GOx@HOF in Example 1 of the present invention and HOF in Comparative Example 1, wherein A is an infrared spectrum; B is an X-ray powder diffraction spectrum; Figure 3 The potential change diagram of the materials prepared in Example 1 and Comparative Example 1 of the present invention; Figure 4 The UV absorption graphs of the materials prepared in Example 1 and Comparative Example 1 of the present invention and chitosan (CS); Figure 5 UV absorption spectra of different groups of materials after reaction with TMB, where Gs represents glucose, laser is 808nm, 1W / cm 2 , 5min; Figure 6 This is the enzyme activity diagram of GOx@HOF-CuS@CS prepared in Example 1 of the present invention; Figure 7 This is the enzyme activity diagram of GOx@HOF-CuS@CS and GOx prepared in Example 1 of the present invention under different treatment conditions, Acetone is acetone, Trypsin is trypsin, and Urea is urea; Figure 8 The activity of S. aureus bacteria after treatment with GOx@HOF+Gs, GOx@HOF-CuS@CS+Gs, and GOx@HOF-CuS@CS+Gs+Laser prepared in Example 1 of the present invention, wherein Gs represents glucose, and the laser is 808 nm, 1 W / cm 2, 5min; Fig. 9 The bacterial activity of E.coil treated with GOx@HOF+Gs, GOx@HOF-CuS@CS+Gs, and GOx@HOF-CuS@CS+Gs+Laser prepared in Example 1 of the present invention, wherein Gs represents glucose, and the laser is 808 nm, 1 W / cm 2 , 5min; Fig.10 The flat plate and data statistics of S. aureus after GOx@HOF, GOx@HOF-CuS@CS, and GOx@HOF-CuS@CS+Laser treatment prepared in Example 1 of the present invention, wherein the laser is 808nm, 1W / cm 2 , 5min; Fig.11 The flat plate and data statistics of E.coil after GOx@HOF, GOx@HOF-CuS@CS, and GOx@HOF-CuS@CS+Laser treatment prepared in Example 1 of the present invention, wherein the laser is 808nm, 1W / cm 2 , 5min; Fig.12 This is a HUVECs cell safety test diagram of GOx@HOF-CuS@CS prepared in Example 1 of the present invention; Fig.13 This is the hemolysis condition of GOx@HOF-CuS@CS prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] Chitosan was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., C766421, CAS: 9012-76-4.

[0024] Example 1 S1: Weigh 5 mg of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) into a 2 mL centrifuge tube, add 500 μL DMF, and place in an ultrasonic cleaner for 30 min to obtain a H4TBAPy solution; weigh 2.5 mg of GOx into a 5 mL centrifuge tube, add 4.5 mL of purified water, disperse evenly, and obtain a GOx solution for later use.

[0025] S2: The GOx solution was quickly added to the H4TBAPy solution, stirred at 800 rpm for 5 min in the dark, and aged for 25 min. After the reaction was completed, the material was washed by centrifugation multiple times at 13,000 rpm for 10 min with purified water until the supernatant was colorless to obtain a GOx@HOF stock solution (1 mg / mL). The enzyme content in GOx@HOF was determined to be 23.04%wt by the BCA method and was set aside.

[0026] S3: Measure 100 mL of purified water and place it in a flask, add 17.75 mg of copper chloride dihydrate, then add 20 mg of sodium citrate, stir for 10 min, and finally add 24 mg of sodium sulfide nonahydrate, stir at 1000 rpm for 10 h. After the reaction is completed, use purified water to centrifuge and wash the material several times at 15000 rpm for 20 min until the supernatant is colorless, and use a vacuum drying oven to dry to obtain CuS for later use.

[0027] S4: Dissolve chitosan in 1% glacial acetic acid solution, stir 5 mg CuS in 5 mL of 5 mg / mL chitosan solution at 1200 rpm for 3 h. After the reaction is completed, use purified water to centrifuge and wash the material at 15000 rpm for 20 min, and dry it in a vacuum drying oven for use.

[0028] S5: 2 mL of GOx@HOF stock solution (1 mg / mL) and 4 mg of CuS@CS were added to 4 mL of purified water, ultrasonically dispersed evenly, and stirred at 1200 rpm for 12 h. After the reaction was completed, the material was centrifuged and washed multiple times with purified water at 11000 rpm for 15 min to obtain GOx@HOF-CuS@CS. The enzyme content was determined by the BCA method to be 7.78%wt.

[0029] Embodiment 2: S1: Weigh 5 mg of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) into a 2 mL centrifuge tube, add 500 μL DMF, and ultrasonicate in an ultrasonic cleaner for 30 min to obtain a H4TBAPy solution; weigh 2.5 mg of GOx into a 5 mL centrifuge tube, add 4.5 mL of purified water, and disperse evenly to obtain a GOx solution for later use.

[0030] S2: The GOx solution was quickly added to the H4TBAPy solution, stirred at 800 rpm for 10 min in the dark, and aged for 20 min. After the reaction was completed, the material was washed by centrifugation multiple times at 12000 rpm for 15 min with purified water until the supernatant was colorless to obtain a GOx@HOF stock solution (1 mg / mL). The enzyme content in GOx@HOF was determined to be 25.16%wt by BCA method and was set aside.

[0031] S3: Measure 100 mL of purified water and place it in a flask, add 15 mg of copper chloride dihydrate, then add 20 mg of sodium citrate, stir at 1000 rpm for 10 min, and finally add 20 mg of sodium sulfide nonahydrate and stir for 10 h. After the reaction is completed, use purified water to centrifuge and wash the material several times at 13000 rpm for 30 min until the supernatant is colorless, and use a vacuum drying oven to dry the obtained CuS to obtain CuS for later use.

[0032] S4: Dissolve chitosan in 1% glacial acetic acid solution, stir 5 mg CuS in 5 mL of 5 mg / mL chitosan solution at 1200 rpm for 3 h. After the reaction is completed, use purified water to centrifuge and wash the material at 13000 rpm for 30 min, and dry it in a vacuum drying oven for use.

[0033] S5: 2 mL of GOx@HOF stock solution (1 mg / mL) and 3.5 mg of CuS@CS were added to 4 mL of purified water, ultrasonically dispersed evenly, and stirred at 1200 rpm for 12 h. After the reaction was completed, the material was centrifuged and washed multiple times with purified water at 11000 rpm for 15 min to obtain GOx@HOF-CuS@CS. The enzyme content was determined by the BCA method to be 9.15%wt.

[0034] Embodiment 3: S1: Weigh 5 mg of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) into a 2 mL centrifuge tube, add 500 μL DMF, and ultrasonicate in an ultrasonic cleaner for 30 min to obtain a H4TBAPy solution; weigh 3.0 mg of GOx into a 5 mL centrifuge tube, add 4.5 mL of purified water, and disperse evenly to obtain a GOx solution for later use.

[0035] S2: The GOx solution was quickly added to the H4TBAPy solution, stirred at 800 rpm for 5 min in the dark, and aged for 25 min. After the reaction was completed, the material was washed by centrifugation multiple times at 13,000 rpm for 10 min with purified water until the supernatant was colorless to obtain a GOx@HOF stock solution (1 mg / mL). The enzyme content in GOx@HOF was determined to be 29.97%wt by BCA method and was set aside.

[0036] S3: Measure 100 mL of purified water and place it in a flask, add 17.75 mg of copper chloride dihydrate, then add 20 mg of sodium citrate, stir at 1000 rpm for 10 min, and finally add 24 mg of sodium sulfide nonahydrate and stir for 10 h. After the reaction is completed, use purified water to centrifuge and wash the material several times at 15000 rpm for 20 min until the supernatant is colorless, and use a vacuum drying oven to dry to obtain CuS for later use.

[0037] S4: Dissolve chitosan in 1% glacial acetic acid solution, stir 5 mg CuS in 5 mL of 5 mg / mL chitosan solution at 1200 rpm for 3 h. After the reaction is completed, use purified water to centrifuge and wash the material at 15000 rpm for 20 min, and use a vacuum drying oven to dry it for subsequent use.

[0038] S5: 1 mL GOx@HOF stock solution (1 mg / mL) and 2 mg CuS@CS were added to 4 mL purified water, ultrasonically dispersed evenly, and stirred at 1200 rpm for 12 h. After the reaction was completed, the material was centrifuged and washed multiple times with purified water at 11000 rpm for 15 min to obtain GOx@HOF-CuS@CS. The enzyme content was determined by the BCA method to be 9.97%wt.

[0039] Embodiment 4: S1: Weigh 5 mg of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) into a 2 mL centrifuge tube, add 500 μL DMF, and place in an ultrasonic cleaner for 30 min to obtain a H4TBAPy solution; weigh 0.5 mg of GOx into a 5 mL centrifuge tube, add 4.0 mL of purified water, and disperse evenly to obtain a GOx solution for later use.

[0040] S2: The GOx solution was quickly added to the H4TBAPy solution, stirred at 800 rpm for 5 min in the dark, and aged for 25 min. After the reaction was completed, the material was washed by centrifugation multiple times at 13,000 rpm for 10 min with purified water until the supernatant was colorless to obtain a GOx@HOF stock solution (1 mg / mL). The enzyme content in GOx@HOF was determined to be 5.72%wt by BCA method and was set aside.

[0041] S3: Measure 100 mL of purified water and place it in a flask, add 15.30 mg of copper chloride dihydrate, then add 15.5 mg of sodium citrate, stir at 1000 rpm for 10 min, and finally add 24 mg of sodium sulfide nonahydrate and stir for 10 h. After the reaction is completed, use purified water to centrifuge and wash the material several times at 15000 rpm for 20 min until the supernatant is colorless, and use a vacuum drying oven to dry to obtain CuS for later use.

[0042] S4: Dissolve chitosan in 0.5% glacial acetic acid solution, stir 5 mg CuS in 3 mL of 5 mg / mL chitosan solution at 1000 rpm for 4 h. After the reaction is completed, use purified water to centrifuge and wash the material at 15000 rpm for 20 min, and use a vacuum drying oven to dry it for subsequent use.

[0043] S5: 2 mL of GOx@HOF stock solution (1 mg / mL) and 3 mg of CuS@CS were added to 4 mL of purified water, ultrasonically dispersed evenly, and stirred at 1200 rpm for 14 h. After the reaction was completed, the material was centrifuged and washed multiple times with purified water at 13000 rpm for 10 min to obtain GOx@HOF-CuS@CS. The enzyme content was determined by the BCA method to be 2.35%wt.

[0044] Embodiment 5: S1: Weigh 5 mg of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene (H4TBAPy) into a 2 mL centrifuge tube, add 500 μL DMF, and ultrasonicate in an ultrasonic cleaner for 30 min to obtain a H4TBAPy solution; weigh 3.5 mg of GOx into a 5 mL centrifuge tube, add 5.0 mL of purified water, and disperse evenly to obtain a GOx solution for later use.

[0045] S2: The GOx solution was quickly added to the H4TBAPy solution, stirred at 800 rpm for 5 min in the dark, and aged for 30 min. After the reaction was completed, the material was washed by centrifugation multiple times at 13,000 rpm for 10 min with purified water until the supernatant was colorless to obtain a GOx@HOF stock solution (1 mg / mL). The enzyme content in GOx@HOF was determined to be 31.24%wt by BCA method and was set aside.

[0046] S3: Measure 100 mL of purified water and place it in a flask, add 37.6 mg of copper chloride dihydrate, then add 40 mg of sodium citrate, stir at 1000 rpm for 10 min, and finally add 48 mg of sodium sulfide nonahydrate and stir for 12 h. After the reaction is completed, use purified water to centrifuge and wash the material several times at 15000 rpm for 20 min until the supernatant is colorless, and use a vacuum drying oven to dry to obtain CuS for later use.

[0047] S4: Dissolve chitosan in 1.5% glacial acetic acid solution, stir 5 mg CuS in 5 mL of 8 mg / mL chitosan solution at 1200 rpm for 2 h. After the reaction is completed, use purified water to centrifuge and wash the material at 15000 rpm for 20 min, and use a vacuum drying oven to dry it for subsequent use.

[0048] S5: 2 mL of GOx@HOF stock solution (1 mg / mL) and 5 mg of CuS@CS were added to 4 mL of purified water, ultrasonically dispersed evenly, and stirred at 1500 rpm for 10 h. After the reaction was completed, the material was centrifuged and washed multiple times with purified water at 11000 rpm for 15 min to obtain GOx@HOF-CuS@CS. The enzyme content was determined by the BCA method to be 9.25%wt.

[0049] Comparative Example 1 5 mg of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene was dissolved in 500 μL of DMF, 4.5 mL of purified water was added, stirred at room temperature for 8 min, kept in dark for 25 min, centrifuged and washed with water to obtain HOF.

[0050] Effect Example 1 Structure Verification The CuS@CS, GOx@HOF, GOx@HOF-CuS@CS obtained in Example 1 of the present application and the HOF obtained in Comparative Example 1 were observed using a transmission electron microscope, and the results are shown in the attached figure. Figure 1 As shown in A, 1B, 1C, and 1D, it is proved that GOx@HOF-CuS@CS was successfully prepared and observed Figure 1 As can be seen from A and 1D, the hydrogen-bonded organic framework encapsulates glucose oxidase, and the morphology of the material does not change significantly.

[0051] The GOx@HOF prepared in Example 1 and the HOF obtained in Comparative Example 1 were subjected to infrared detection and X-ray powder diffraction. The results are as follows: Figure 2 As described above, it is proved that after the hydrogen bond organic framework encapsulates glucose oxidase, the structure of the organic framework does not change.

[0052] The zeta potential of HOF prepared in Comparative Example 1, GOx@HOF prepared in Example 1, copper sulfide prepared in Example 1, CuS@CS prepared in Example 1 and GOx@HOF-CuS@CS prepared in Example 1 were measured. The results are shown in the attached figure. Figure 3 As shown in the figure, the potential of GOx@HOF-CuS@CS is -16.36 mV. The negative potential with a large absolute value enables GOx@HOF-CuS@CS to be stably dispersed in aqueous solution.

[0053] Ultraviolet absorption tests were performed on chitosan, GOx@HOF prepared in Example 1, copper sulfide prepared in Example 1, HOF prepared in Comparative Example 1, CuS@CS prepared in Example 1, and GOx@HOF-CuS@CS prepared in Example 1. The results are as follows: Figure 4 As shown in the figure, the ultraviolet absorption peak of HOF is highly overlapped with that of GOx@HOF, which further proves that the encapsulation of glucose oxidase by the hydrogen-bonded organic framework has little effect on the structure of the hydrogen-bonded organic framework. By comparing the ultraviolet absorption peaks of GOx@HOF, CuS@CS and GOx@HOF-CuS@CS, the successful preparation of GOx@HOF-CuS@CS was verified.

[0054] Effect Example 2 In order to verify the chemical kinetics of the antibacterial composite material, the present application uses 3,3',5,5'-tetramethylbenzidine (TMB) as a probe to evaluate the catalytic activity of GOx@HOF-CuS@CS prepared in Example 1 by comparing different groups.

[0055] Five groups of experiments were set up, and the contents of the components in the reaction system (the solvents were all 0.01 mol / L PBS solution) were shown in Table 1: After the samples were prepared, they were incubated at 37°C for 2 h. The fifth group was illuminated with 808 nm near-infrared light (1.0 W·cm -2 ) were irradiated for 5 min, and the absorption spectrum at 400-800 nm was detected by UV-vis. The chemical kinetics of the antibacterial composite materials were compared based on the absorption value at 652 nm.

[0056] The results are as follows Figure 5 As shown, the GOx@HOF-CuS@CS material disclosed in this application has a photodynamic effect, and photothermal therapy can promote the photodynamic effect.

[0057] Effect Example 3 Enzyme Stability Test In order to verify the enzyme stability of the antibacterial composite material, the present application verifies the enzyme stability at different times and under different conditions by using titanium sulfate test solution.

[0058] The GOx@HOF-CuS@CS solution prepared by the method described in Example 1 was prepared into a 1 mg / mL solution and placed at 4°C for 14 days. During this period, samples were taken at the same time every day. The GOx@HOF-CuS@CS solution with a concentration of 50 μg / mL was incubated with 10 mM glucose at 37°C for 2 h. Subsequently, 200 μL of the sample was taken and 200 μL of titanium sulfate detection solution (6 μg / mL) was added. The generation of H2O2 at 415 nm was detected by ultraviolet light to evaluate the enzyme stability. The results are shown in the attached figure. Figure 6 shown.

[0059] Free GOx and GOx@HOF-CuS@CS were respectively prepared into 1. 1 mg / mL aqueous solution (60°C); 2. 1 mg / mL acetone solution; 3. 1 mg / mL aqueous solution containing 6M urea; 4. 1 mg / mL aqueous solution containing 5mM pancreatin. After 30 minutes of treatment, 20 μL of the sample described in 1-4 was added to 400 μL PBS containing 10mM glucose and reacted at 37°C for 2 hours. Then 200 μL of the sample was taken and 200 μL titanium sulfate detection solution (6 μg / mL) was added. The generation of H2O2 was detected by ultraviolet light to evaluate the enzyme stability. The results are shown in the attached figure. Figure 7shown.

[0060] The results show that the antibacterial composite material of the present application has excellent enzyme stability.

[0061] Effect Example 4 Bacteria Test In order to verify the antibacterial effect of the antibacterial composite material, the growth inhibition ability of materials with different concentrations on Staphylococcus aureus (S. aureus) and Escherichia coli (E. coil) was detected by OD value.

[0062] Staphylococcus aureus and Escherichia coli on agar medium were transferred to liquid Luria-Bertani (LB) medium, which was shaken at 200 rpm at 37 °C for 8 h. The bacteria were then collected by centrifugation and diluted to 1 × 10 in 48-well plates using LB medium containing 10 mM glucose. 8 CFU / mL. 1 μL PBS was added as a negative control group; 1 μL of GOx@HOF solution prepared in Example 1 with different concentrations, and 1 μL of GOx@HOF-CuS@CS solution prepared in Example 1 with different concentrations, so that the concentrations of the corresponding materials in the 48-well plate were 10, 25, 50, 75, and 100 μg∙mL -1 The culture medium containing GOx@HOF-CuS@CS was divided into two groups. One group was illuminated by near-infrared light at 808 nm (1.0 W·cm -2 ) for 5 min, and incubate the plate at 37°C and 200 rpm on a bacterial shaker. After 4 h, the absorbance at 600 nm was measured to assess the bacterial concentration. The results are shown in the attached figure. Figure 8 , Attachment Fig. 9 shown.

[0063] The results showed that under the irradiation of 808nm near-infrared light, the bacterial activity of both Staphylococcus aureus and Escherichia coli decreased significantly under the action of GOx@HOF-CuS@CS at a concentration of 100μg / mL, proving that the antibacterial composite material can inhibit bacterial growth and has excellent broad-spectrum antibacterial effect.

[0064] Effect Example 5: Bacterial Plate Test In order to further verify the antibacterial effect of the antibacterial composite material, the bactericidal ability of different groups against Staphylococcus aureus and Escherichia coli was verified by the plate counting method. The GOx@HOF and GOx@HOF-CuS@CS used were prepared in Example 1.

[0065] Staphylococcus aureus and Escherichia coli stored in frozen glycerol were transferred to liquid Luria-Bertani (LB) medium and shaken at 200 rpm for 10 h at 37 °C in a bacterial shaker. The bacteria were then collected by centrifugation and diluted to 1×10 using 1. LB medium containing 100 μg / mL GOx@HOF and 10 mM glucose; 2. LB medium containing 100 μg / mL GOx@HOF-CuS@CS and 10 mM glucose; 3. LB medium containing 10 mM glucose. 8 CFU / mL, and then incubated at 37°C and 200 rpm for 4 h. The culture medium containing GOx@HOF-CuS@CS was divided into two groups. One group was illuminated by near-infrared light at 808 nm (1.0 W·cm -2 ) for 5 min. After incubation, the bacterial suspension was diluted with LB medium to 1×10 5 Then, 100 μL of the diluted bacterial suspension was spread on the solid culture medium through glass beads and incubated at 37°C for 12 h before recording the number of colonies. The results are shown in the attached figure. Fig.10 and attached Fig.11 The results showed that the PBS, GOx@HOF, and GOx@HOF-CuS@CS groups all had obvious colonies, and under the irradiation of 808nm near-infrared light, the bactericidal rates of the antibacterial composite materials against Staphylococcus aureus and Escherichia coli reached more than 99%.

[0066] Effect Example 6: Biocompatibility Evaluation The GOx@HOF-CuS@CS used in this effect example is prepared in Example 1.

[0067] In order to evaluate the biocompatibility of normal cells with GOx@HOF-CuS@CS, human umbilical vein endothelial cells (HUVECs) were seeded in 96-well plates (8000 cells / well) and cultured with DMEM medium. They were incubated at 37 °C under normoxic conditions (O2 21%) for 24 h. The original medium was discarded and GOx@HOF-CuS@CS with concentrations of 0, 5, 10, 25, 50, 75, and 100 μg∙mL were added. -1 The cells were incubated for 24 h in DMEM medium and the cell survival rate was detected by standard CCK-8 method. Fig.12 As shown, it is demonstrated that GOx@HOF-CuS@CS has good biocompatibility.

[0068] Mix 100 μL of heparin with 900 μL of saline, take 20 μL of heparin solution and add it to a centrifuge tube. Use a capillary tube soaked in heparin solution to collect blood from the canthus, and drop the blood into a centrifuge tube filled with heparin for anticoagulation. Centrifuge at 3500 rpm for 10 min, remove the upper plasma, and wash the blood cells with pH 7.4 PBS (10 mM) until there is no foam in the supernatant. 760 μL of GOx@HOF-CuS@CS with different concentrations (10, 25, 50, 100, 200, 400, 500 μg∙mL -1 40 μL of red blood cells were added to PBS (10 μL); 40 μL of red blood cells were added to 760 μL PBS and deionized water as negative / positive control groups, respectively. All the above samples were incubated at room temperature for 30 min, centrifuged and photographed, and the supernatant was collected. The ultraviolet absorbance at 570 nm was measured with a UV-Vis spectrophotometer. The hemolysis results are shown in the attached figure. Fig.13 As shown, the hemolysis rate (Hemolysis) is calculated as follows: Among them A sample is the absorbance value of the sample, A negative and A positive The absorbance values ​​of negative samples and positive samples are shown in Figure 2. The results show that the antibacterial composite material has preliminary biocompatibility.

[0069] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art may still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An antibacterial composite material based on a hydrogen bond organic framework, characterized in that: The composite material is mainly composed of a hydrogen bond organic framework, glucose oxidase is encapsulated in the main body, and copper sulfide wrapped by chitosan is adsorbed on the surface; The building block of the hydrogen bond organic framework is 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene.

2. The antibacterial composite material based on hydrogen bond organic framework according to claim 1, characterized in that: The loading amount of glucose oxidase in the composite material is 2.35%wt-9.97%wt.

3. A method for preparing an antibacterial composite material based on a hydrogen bond organic framework as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1: 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene is dissolved in solvent I as solution A, and glucose oxidase is dispersed in water as solution B; S2: quickly add solution B prepared in S1 into solution A, stir for 5-10 minutes, place in the dark for 20-30 minutes, centrifuge and wash with water to obtain GOx@HOF; S3: Add copper chloride and sodium citrate to water in sequence, stir evenly, then add sodium sulfide, stir for 10-12 hours, centrifuge, wash with water, and dry to obtain copper sulfide; S4: Disperse the copper sulfide obtained in S3 in the chitosan solution and stir at 1000-1200 rpm for 2-4 hours, centrifuge, wash with water, and dry to obtain CuS@CS; S5: Add GOx@HOF obtained in S2 and CuS@CS obtained in S4 into water, disperse them evenly by ultrasonication, stir at 1200-1500 rpm for 10-14 h, centrifuge and wash with water to obtain GOx@HOF-CuS@CS.

4. The method for preparing an antibacterial composite material based on a hydrogen bond organic framework according to claim 3, characterized in that: The mass ratio of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene to glucose oxidase in S2 is 1:0.1-0.7; The molar ratio of copper chloride: sodium citrate: sodium sulfide in S3 is 0.9-1.1:0.6-0.9:1; The mass ratio of copper sulfide to chitosan in S4 is 1:3-8; The mass ratio of GOx@HOF to CuS@CS in the S5 is 1:1.5-2.

5.

5. The method for preparing an antibacterial composite material based on a hydrogen bond organic framework according to claim 3, characterized in that: The solvent I is selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; the volume ratio of solution A to solution B in S2 is 1:8-10; the mass volume ratio of GOx@HOF to water in S5 is 4 mg:5-20 mL.

6. The method for preparing an antibacterial composite material based on a hydrogen bond organic framework according to claim 3, characterized in that: In S2, the centrifugal speed is 12000-13000rpm and the centrifugal time is 10-15min; In S3, the centrifugal speed is 13000-15000rpm and the centrifugal time is 20-30min; In S4, the centrifugal speed is 13000-15000rpm and the centrifugal time is 20-30min; In S5, the centrifugal speed is 11000-13000rpm and the centrifugal time is 10-15min.

7. The method for preparing an antibacterial composite material based on a hydrogen bond organic framework according to claim 3, characterized in that: The concentration of sodium citrate in S3 is 0.1-0.4 mg / mL.

8. The method for preparing an antibacterial composite material based on a hydrogen bond organic framework according to claim 3, characterized in that: The chitosan solution in S4 is prepared by dissolving chitosan in a 0.5-1.5% glacial acetic acid solution, and the concentration of chitosan is 5-50 mg / mL.

9. The method for preparing an antibacterial composite material based on a hydrogen bond organic framework according to claim 3, characterized in that: The mass ratio of 1,3,6,8-tetrakis(4-carboxyphenyl)pyrene to glucose oxidase in S2 is 1:0.5; The molar ratio of copper chloride: sodium citrate: sodium sulfide in S3 is 1.05:0.78:1 The mass ratio of copper sulfide to chitosan in S4 is 1:5; The mass ratio of GOx@HOF to CuS@CS in S5 is 1:

2.

10. Use of the antibacterial composite material based on hydrogen-bonded organic framework as claimed in claim 1 or 2 in the preparation of antibacterial drugs.

Citation Information

Patent Citations

  • Porous frame material for storing, transporting and preparing biological products

    CN108456241A

  • Method for preparing glucose oxidase-modified metal organic framework pharmaceutical composition

    CN110585169A

  • Chitosan / manganese dioxide / glucose oxidase nano composite material as well as preparation and application thereof

    CN114984241A

  • Manganese-based metal organic framework material loaded glucose oxidase composite nanomaterial as well as preparation method and application thereof

    CN115040649A

  • Hydrogen bond organic framework enzyme biological composite material as well as preparation method and application thereof

    CN116409885A